TD-LTE and LTE FDD fusion networking strategy - Lunsuo WANG (Dianxin kexue)
With the rapid development of mobile internet,as well as the rapid expansion of the scale of 4G network,the frequency resources worldwide are increasingly scarce.Learning from the successful experience of the development of TD-LTE and LTE FDD fusion,the challenges faced by the development of the integration of networking strategy and TD-LTE international development were analyzed,the development mode and strategy of TDD and FDD were proposed,and the future development targeted recommendations of the communication operator network was put forward.The TD-LTE and LTE FDD convergence has become a big trend.As the strategic layout of the communications operators,4G network using LTE network approach,should be taken into account in the LTE master plan in advance.